C5a induces caspase‐dependent apoptosis in brain vascular endothelial cells in experimental lupus. Issue 4 (11th July 2016) - Mahajan, Supriya D.; Tutino, Vincent M.; Redae, Yonas; Meng, Hui; Siddiqui, Adnan; Woodruff, Trent M.; Jarvis, James N.; Hennon, Teresa; Schwartz, Stanley; Quigg, Richard J.; Alexander, Jessy J.
Summary: Blood–brain barrier (BBB) dysfunction complicates central nervous system lupus, an important aspect of systemic lupus erythematosus. To gain insight into the underlying mechanism, vascular corrosion casts of brain were generated from the lupus mouse model, MRL/ lpr mice and the MRL/MpJ congenic controls. Scanning electron microscopy of the casts showed loss of vascular endothelial cells in lupus mice compared with controls. Immunostaining revealed a significant increase in caspase 3 expression in the brain vascular endothelial cells, which suggests that apoptosis could be an important mechanism causing cell loss, and thereby loss of BBB integrity. Complement activation occurs in lupus resulting in increased generation of circulating C5a, which caused the endothelial layer to become 'leaky'. In this study, we show that C5a and lupus serum induced apoptosis in cultured human brain microvascular endothelial cells (HBMVECs), whereas selective C5a receptor 1 (C5aR1) antagonist reduced apoptosis in these cells, demonstrating C5a/C5aR1‐dependence. Gene expression of initiator caspases, caspase 1 and caspase 8, and pro‐apoptotic proteins death‐associated protein kinase 1, Fas‐associated protein (FADD), cell death‐inducing DNA fragmentation factor 45 000 MW subunit A‐like effector B (CIDEB) and BCL2‐associated X protein were increased in HBMVECs treated with lupus serum or C5a, indicating that both the intrinsic and extrinsic apoptotic pathways could be critical mediators of brain endothelial cell apoptosis in this setting. Overall, our findings suggest that C5a/C5aR1 signalling induces apoptosis through activation of FADD, caspase 8/3 and CIDEB in brain endothelial cells in lupus. Further elucidation of the underlying apoptotic mechanisms mediating the reduced endothelial cell number is important in establishing the potential therapeutic effectiveness of C5aR1 inhibition that could prevent and/or reduce BBB alterations and preserve the physiological function of BBB in central nervous system lupus. Abstract : Brain vascular endothelial cell number is reduced in lupus, with a significant increase in caspase 3 expression indicating that apoptosis could be an important mechanism causing loss of BBB integrity in this setting. Brain endothelial cell apoptosis occurs via activation of FADD, caspase 8/3 and CIDEB, and is caused by complement activation by product, C5a which is increased in lupus.